Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 2 - Section 2.2 - The Multiplication Property of Equality - Exercise Set - Page 110: 31



Work Step by Step

$\dfrac{3}{4}t-\dfrac{1}{2}=\dfrac{1}{3}$ Add $\dfrac{1}{2}$ to both sides of the equation: $\dfrac{3}{4}t-\dfrac{1}{2}+\dfrac{1}{2}=\dfrac{1}{3}+\dfrac{1}{2}$ $\dfrac{3}{4}t=\dfrac{2+3}{6}$ $\dfrac{3}{4}t=\dfrac{5}{6}$ To get the solution, multiply both sides of the equation by $\dfrac{4}{3}$: $\Big(\dfrac{3}{4}t\Big)\Big(\dfrac{4}{3}\Big)=\dfrac{5}{6}\Big(\dfrac{4}{3}\Big)$ $t=\dfrac{20}{18}=\dfrac{10}{9}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.